Does Nigerian Low-Income Families Need For Micro Family Takaful Scheme? - SHA’ABAN, MURTALA MUHAMMAD; SALLEH, FAUZILAH (The journal of contemporary issues in business and government, 2021)
Insurance, beyond doubt, is an essential policy for poverty eradication. Since low income households can't afford the high insurance premium, the best protection is Microinsurance or Microtakaful. In terms of principle, Microtakaful is barely the same as Takaful, except that the former is based on mutual contribution with affordable price that overcomes a specific risk that plagues the low income households. Having that said, this study proposes Microtakaful as an essential mechanism that protects the low-income group, apart from reducing the poverty rate. The proposed Microtakaful framework consists of a protection scheme equipped with financial support grants from the government, non-governmental organisations (NGOs), charity institutions, waqaf, international charity organisations, and donor agencies. This offers a basis to further look into the Microtakaful product and mutual pricing model designs based on cooperative principles as a mobilisation fund aimed at eradicating poverty amidst low-income families.